Epidermis foliar de Glycine soja Sieb. y Zucc. - Flores, Eugenia M. (1977)
Electron scanning microscopy of the adaxial and abaxial leaf epiderm is of Glycine soja showed the same kinds of trichomes on the veins: a large, uniseriate and vesicular hair and a short, multicellular and glandular trichome; the latter also occurs on the abaxial areoles. Leaves are amphistomatic arid have abundant stomata of the paracytic type; the ostioles are small and become reduced to the stomatic chamber. Areoles are irregular, mostly polygonal, and the veinlets divide several times. The cuticle is rough.